2002
DOI: 10.1017/s0013091500001097
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Ideals in the Algebra of Operators on Certain Banach Spaces

Abstract: For a Banach space X, let B(X) denote the Banach algebra of all continuous linear operators on X. First, we study the lattice of closed ideals in B(Jp), where 1 < p < ∞ and Jp is the pth James space. Our main result is that the ideal of weakly compact operators is the unique maximal ideal in B(Jp). Applications of this result include the following. (ii) For each natural number n and each n-tuple (m 1 , . . . , mn) in {k 2 | k ∈ N} ∪ {∞}, there is a Banach space X such that B(X) has exactly n maximal ideals, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
(24 reference statements)
0
28
0
Order By: Relevance
“…: Suppose that PAG F ðEÞ: Then in fact PAG F ðEÞ by [22,Proposition 3.4], and so P ¼ P n j¼1 S j R j for some nAN; R 1 ; y; R n ABðE; F Þ; and S 1 ; y; S n ABðF ; EÞ: Clearly, the operators R : x/ðR 1 x; y; R n xÞ; E-F "n ; and S : ðx 1 ; y; x n Þ/ P n j¼1 S j x j ; F "n -E; satisfy P ¼ SR: This implies by Laustsen [22, Lemma 3.6(ii)] that Q :¼ RSRSABðF "n Þ is idempotent with im QDim P:…”
Section: Operators On C 0 -Direct Sumsmentioning
confidence: 99%
See 3 more Smart Citations
“…: Suppose that PAG F ðEÞ: Then in fact PAG F ðEÞ by [22,Proposition 3.4], and so P ¼ P n j¼1 S j R j for some nAN; R 1 ; y; R n ABðE; F Þ; and S 1 ; y; S n ABðF ; EÞ: Clearly, the operators R : x/ðR 1 x; y; R n xÞ; E-F "n ; and S : ðx 1 ; y; x n Þ/ P n j¼1 S j x j ; F "n -E; satisfy P ¼ SR: This implies by Laustsen [22, Lemma 3.6(ii)] that Q :¼ RSRSABðF "n Þ is idempotent with im QDim P:…”
Section: Operators On C 0 -Direct Sumsmentioning
confidence: 99%
“…Laustsen has proved that this maximal ideal is the only maximal ideal in BðJÞ; and applied this result to construct Banach spaces E such that BðEÞ has any specified finite number of maximal ideals of any specified codimensions (see [22]). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laustsen [25,26] has subsequently shown that W (J 2 ) is the unique maximal ideal in B(J 2 ), while the scalar multiples of the character are the only traces on B(J 2 ). (vi) Giesy and James [20] have shown that c 0 is finitely representable in J 2 , that is, for each ε > 0 and each n ∈ N, there is an operator T :…”
mentioning
confidence: 99%